Genetic dissection of disease resistance trait in rubber tree (Hevea brasiliensis) through QTL mapping - Roy C.B; Kilian Andrzej; Madhavan J; Saha T (International Rubber Conference & IRRDB Annual Meeting 2017: Current and Future Challenges in Natural Rubber Industry: Capturing Opprtunities in the Green Economy, 18-20 October 2017, Jakarta, Indonesia. p. 34.)
Abnormal leaf fall disease caused by Phytophthora meadii and Corynespora leaf disease caused by Corynespora cassiicola are the two major diseases of rubber (Hevea brasiliensis) in India causing significant loss to rubber production. Identifying genes conferring tolerance to these fungal diseases is highly desired for resistance breeding in rubber. Resistance traits are mainly quantitative in nature and are determined by many genes, which are described as quantitative trait loci (QTL). Genetic markers have made it possible to detect QTLs that are significantly associated with traits. Construction of a linkage map, densely populated with molecular markers, is essential for dissection of QTL for disease resistance trait. An interspecific cross between H. brasiliensis (clone RRII 105) and H. benthamiana (clone F 4542) with varying levels of disease resistance was made and a progeny population was raised for construction of a linkage map. RRII 105 is a commercially cultivated high yielding clone with moderate level of susceptibility to P. meadii and high level of susceptibility to C. cassiicola. F4542 is a low yielder with high level of tolerance to both P. meadii and C. cassiicola. Genotyping of the mapping population comprising 86 progenies along with two parents was carried out using co-dominant SNP markers and dominant silico DArT markers derived from DArT sequencing (DArTseqTRA). A linkage map with the DArTseq data was constructed using DArT PLS OCD MAPPING program. Kosambi mapping function was used to estimate genetic distances. A linkage map was produced for each parent by combining the relevant silico DArT and SNP markers. A consensus map was created using 24004 markers, which aasembled into 18 linkage groups, thus reflecting the haploid chromosome number of Hevea (n=18). An average of 1334 markers per chromosome was estimated with an average inter marker distance of 0.15 cM and total map distance was calculated as 3709 cM. Phenotyping for disease resistance to both P. meadii and C. cassiicola infections was carried out for the parents and 86 progeny population. Zoospores from a virulent isolate of P. meadii was used for in vitro challenge inoculation on leaves of each individual followed by measuring the lesion size periodically from 72-120 hours to assess disease reaction. Toxin-based screening methodology was employed to check for disease resistance to C. cassiicola. WIlting intensity on the tender leaves due to the effect of toxin was assessed 24 hours following the toxin treatment. Assessment for disease response clearly discriminated progenies with varying levels of resistance reactions to both P. meadii and C. cassiicola. Progenies with extreme levels of tolerance and susceptibility were identified along with the majority of the population showing moderate level of resistance/susceptibility. Frequency distribution of disease resistance among the progeny was continuous indicating their quantitative nature of inheritance. In order to identify QTL markers conferring resistance to these fungal diseases, genotypic and phenotypic data for disease resistance from the progeny population were merged and analyzed. Six QTL markers for Phytophthora disease resistance [five mapped in linkage group (LG) 9 and one in LG 15] and seven for Corynespora disease resistance (one each mapped in LG 6, 11, 13 and two each in LG 8 and 16) were identified at an adjusted P value cut off 0.001 and a LOD threshols score of 3. The identified potential QTL markers need to be validated prior to their use in early selection of hybrid clones for tolerance to these fungal diseases.
Keywords: Disease resistance; Genetic dissection; QTL mapping